Pengaruh penggunaan Media Audio visual terhadap hasil belajar Matematikapada materi Bangun ruang di kelas VI MI Persis Gandok - Rohman, Taufik; Risa Nuri Sahar (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The use of learning media, especially Audio Visual Media, is still very low in Mathematics learning. In the learning process carried out, teachers predominantly use the lecture method without using learning media. This causes the learning outcomes obtained by students to not be optimal. From these problems, teachers need to make efforts so that student learning outcomes can reach the KKM. One effort that can be made is to use Audio Visual Media which can help present facts or concepts in a real way, so that students will more easily understand the learning provided well. This research aims to determine the effect of using audio-visual media on Mathematics learning outcomes in Building Space material in class VI MI Persis Gandok. This research uses a pre-experimental design method, one group pretest - posttest design. The sampling technique that will be used by researchers is Purposive Sampling with a sample size of 26 class VI B students. The research instrument is an essay description test with 20 questions which are analyzed by two Mathematics Experts. After being tested and analyzed by experts, the research instrument used was 10 essay questions which were used as test questions. The research results showed that the average Pre-test score was 73.58 and the Posttest score was 85.65, with a significance value in the Pre-test of 0.308 and the Posttest of 0.372. This means that the Sig. > 0.05 and the data can be said to be normally distributed with a Sig value. overall the homogeneity test is 0.201 > 0.05. Hypothesis testing with the t-test obtained a Sig value. (2-tailed) is 0.000 where the Sig value. smaller than 0.05 (0.000 < 0.05), then Ha is accepted and H0 is rejected. This shows that there is an influence of the use of Audio Visual media on Mathematics learning outcomes in Building Space material in Class VI MI Persis Gandok.